Boundary-discontinuous Fourier analysis of simply supported cross-ply plates - Sinan Oktem, A.; Alankaya, Veysel; Guedes Soares, C. (ELSEVIER SCIENCE INC, 2013)
A new higher order theory based analytical solution to the static analysis of general cross-ply plates is presented. The boundary-discontinuous generalized double Fourier series approach is used to solve highly coupled linear partial differential equations with the mixed type simply supported boundary conditions prescribed on the edges. The present results will provide data for the unsolved boundary conditions and provide benchmark comparisons for early design stages and verifications of numerical results such as finite element and boundary element. Analytical results are compared with finite element counterparts using commercially available software under uniformly distributed load. Present results are in good agreement with the finite element counterparts. The effects of important parameters such as lamination scheme, material property, thickness effects as well as their interactions are investigated in detail. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Cross-ply plates; Boundary discontinuous Fourier; Higher order theory; Mixed simply supported; DOUBLY-CURVED PANELS; HIGHER-ORDER THEORY; 3-DIMENSIONAL ELASTICITY SOLUTIONS; FREE-VIBRATION ANALYSIS; MODERATELY-THICK; STATIC ANALYSIS; LAMINATED COMPOSITE; FREQUENCY-RESPONSE; RECTANGULAR-PLATES; CYLINDRICAL PANELS; Engineering; Mathematics; Mechanics